Addressing Challenges Encountered by English Language Teachers in Imparting Communication Skills among Higher Secondary Students: A Critical Overview - Jiby, Jose E; Akkara, Sherine (Transactions on Engineering and Computing Sciences, 2024)
Acquisition and extension of communication skills in the English language is a gateway to academic achievements and professional success. English language communicative competence is a necessary prerequisite in a globally interconnected and communicatively-driven world. This is an imperative for the academic, professional and personal growth. However, English language teachers experience varied challenges in developing effective communication skills among higher secondary students. Hence, the objective of the study is to explore the pedagogical practices in English language communication among the higher secondary students and the obstacles encountered by the teachers. The details are collected through in-depth interviews and focus group discussions using the qualitative framework. The participants represent the tutors who teach at higher secondary levels in and follow the SCERT curriculum. Using purposive sampling, the interview and the focus group discussion have been carried out directly, and the data have been analyzed thematically. The study explores diverse factors and nuances that deter educators in the discipline of language training and verbal proficiency.